Analysis of Economic Growth of the Republic of Uzbekistan - Leonidovna, Mitrushova Marina; Khabibulaevna, Gulomova Nigora; Khabibulaevna, Gulomova Nigora (International Journal of Psychosocial Rehabilitation, 2020)
The most important characteristic of the country's social and economic development belongs to economic growth. This article analyzes the indicators of the economic growth rate of gross domestic product and gross regional product. After calculating the required annual growth rate when doubling the gross domestic product for 15 years, its volumes are calculated for doubling. The dynamics of changes in the structure of GDP for 1995-2018 is presented. The analysis of the rates of regional economic growth and growth, as well as the processing of data on GDP and GRP by grouping methods. The regional structure of the GRP for the main sectors of the economy is presented. Based on the study, a conclusion is drawn.